Strategic Leadership and VUCA environment (Volatile, Uncertain, Complex and Ambiguous) - ZAMANI, Haddou; AIT SOUDANE, Jalila (Revue Internationale des Sciences de Gestion, 2022)
The VUCA environment is characterized by a variety of challenges, including wicked problems, which could sometimes occur simultaneously, putting Leaders in difficulty, mainly at the Strategic Level. In this regard, this article aims to contribute to the literature review through the definition and the development of the purely Anglo-Saxon concepts "VUCA" and "Wicked problems" on one hand; and to put at the disposal of the Strategic Leaders, particularly for the Moroccan large organizations, the American conceptual model based on a systemic analysis of the internal and external environments on the other hand. Therefore, these Strategic Leaders have to better understand the environment at the strategic level, both internal and external, in order to develop a clear, realistic, and evolving vision to design and plan appropriate strategies to ensure the competitiveness and sustainability of their organizations. This requires minimum requisites of SL, including personal and interpersonal skills combined with conceptual competencies, such as systemic thinking and analysis, critical and creative thinking, and innovation in line with an effective implementation of control and oversight mechanisms.